A social network analysis on organizational commitment in Malaysia - Nur Syahidah, Yusoff; Maman Abdurachman, Djauhari; Ebi Shahrin, Suleiman (IEEE, 2012)
This paper deals with social network approach to understand an organizational management problem. Four groups of factors, i.e., workplace spirituality, affective commitment, continuance commitment and normative commitment are used to quantify the level of organizational commitment. In total, there are forty measurements representing those factors. To analyze which factors that strongly influence the level of organizational commitment, social network approach is used where each measurement is considered as a member of social group and the relationship among them as social relationship. To illustrate the advantage of this approach, a case study on the level of organizational commitment in Malaysia will be presented and discussed.